Prevention and Treatment of Radiation-Induced Esophagitis With Oral Herbal Medicine: A Systematic Review and Meta-Analysis - Jae Joon Ha KMD; Sung Eun Hong KMD; Jee Young Lee KMD, PhD; In-Hyuk Ha KMD, PhD; Yoon Jae Lee KMD, PhD (Integrative Cancer Therapies)
Background: Radiation therapy is commonly used for the curative or palliative treatment of lung, esophageal, breast, or mediastinal tumors, with radiation-induced esophagitis (RIE) being a prevalent adverse event. Despite its high incidence, no cure has been identified for RIE, and validated treatment methods remain elusive. This systematic review explores global clinical research on herbal medicines for RIE treatment, assessing their efficacy in prevention and treatment. Methods: A comprehensive literature search across 5 databases targeted randomized controlled clinical trials (RCTs). RCTs published before June 2024 were eligible if they investigated herbal medicine use for RIE prevention or treatment. Using Cochrane methodology and RevMan 5.4 software, a meta-analysis was conducted, and the certainty of evidence was evaluated with the GRADE system. Results: Following the literature selection process, 81 RCTs with 7283 patients were included in the analysis. All studies administered herbal medicine to the treatment group and usual care with conventional medicine to the control group. Meta-analysis revealed that, in terms of overall incidence rate, herbal medicine demonstrated a significantly greater preventive effect compared to usual care (relative risk [RR]: 0.71; 95% CI: 0.65–0.78). Similarly, herbal medicine showed superior efficacy in improving RIE treatment outcomes compared to usual care (RR: 1.29; 95% CI: 1.21–1.38). Herbal medicine exhibited a comparable safety profile with fewer gastrointestinal adverse events and no significant liver toxicity. Conclusions: Herbal medicine demonstrated significant benefits in reducing RIE incidence, delaying onset, alleviating symptoms, and shortening duration in patients undergoing radiation therapy for thoracic malignancies. However, due to limited certainty of the evidence, well-designed, large-scale RCTs are essential to establish the clinical effectiveness of herbal medicine for prevention and treatment, ensuring high-quality evidence for incidence rate and treatment effective rates.